(untitled) (International Journal of Environmental Sciences, 2025)
The study aims to identify the factors influencing green logistics development in Vietnam. The empirical data were collected through 437 questionnaires surveyed by logistics enterprises in Vietnam. Using exploratory factor analysis, confirmatory factor analysis, and structural equation modeling (SEM), the study found that the most influential factor on green logistics development is state policy, while the least impact comes from employees’ awareness and knowledge. The results suggest effective solutions to enhance green logistics development in Vietnam in the future.